Magic Duo Pen Company - Usman, Norsakina; Awang, Salmah; Upilin, Siti Zulaikha; Bakram, Nur Syazwana Syahira (2016)
In this business plan, we are from Magic Duo Pen Company that was involve in manufacturing activities where we are try to come out with an innovate a pen become a multifunction item that has with a lipstick, mascara, and eyeliner to fulfil the demand from a customer and come out with the solution of problem occurs. Apart from that, we choose this type of business because we want to overcome people problem especially to ladies that facing a difficulties to bring their various types of cosmetic in their handbag. So, our company make this product to enhancing their can carry this magic duo pen easily at everywhere together with the stationary and they cosmetic accessories. Our selling price of the product was very affordable and suitable for all level of income. Our company will establish on 15th of January 2018 and located at , 1 Borneo Hypermall, Kota Kinabalu. While, our factoring and office building was allocated at KKIP Selatan, Taman Perindustrian Kota Kinabalu, 89200 Kota Kinabalu, Sabah. Our objective is come out with a variety product that existing in the market. Our main purpose of preparing this business plan is to ensure that our business proposal can be approved by bank.